Stem Cell Therapy for Alzheimer's Disease - M.E. Abdel-Salam, Omar (CNS & Neurological Disorders - Drug Targets, 2011)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder which impairs the memory and intellectual abilities of the affected individuals. Loss of episodic as well as semantic memory is an early and principal feature. The basal forebrain cholinergic system is the population of neurons most affected by the neurodegenerative process. Extracellular as well as intracellular deposition of β- amyloid or Abeta (Aβ) protein, intracellular formation of neurofibrillary tangles and neuronal loss are the neuropathological hallmarks of AD. In the last few years, hopes were raised that cell replacement therapy would provide cure by compensating the lost neuronal systems. Stem cells obtained from embryonic as well as adult tissue and grafted into the intact brain of mice or rats were mostly followed by their incorporation into the host parenchyma and differentiation into functional neural lineages. In the lesioned brain, stem cells exhibited targeted migration towards the damaged regions of the brain, where they engrafted, proliferated and matured into functional neurones. Neural precursor cells can be intravenously administered and yet migrate into brain damaged areas and induce functional recovery. Observations in animal models of AD have provided evidence that transplanted stem cells or neural precursor cells (NPCs) survive, migrate, and differentiate into cholinergic neurons, astrocytes, and oligodendrocytes with amelioration of the learning/memory deficits. Besides replacement of lost or damaged cells, stem cells stimulate endogenous neural precursors, enhance structural neuroplasticity, and down regulate proinflammatory cytokines and neuronal apoptotic death. Stem cells could also be genetically modified to express growth factors into the brain. In the last years, evidence indicated that the adult brain of mammals preserves the capacity to generate new neurons from neural stem/progenitor cells. Inefficient adult neurogenesis may contribute to the pathogenesis of AD and other neurodegenerative disorders. An attempt at mobilizing this endogenous pool of resident stem-like cells provides another attractive approach for the treatment of AD. Studies in patients with AD indicated decreased hippocampal volume derived by neurodegeneration. Intriguingly, many drugs including antidepressants, lithium, acetyl cholinesterase inhibitors, and ginkgo biloba, were able to enhance the impaired neurogenesis in this disease process. This paved the way towards exploring the possible pharmacological manipulation of neurogenesis which would offer an alternative approach for the treatment of AD.
Keywords: stem cells